Characterization of myeloproliferative neoplasms in the paediatric and young adult population. (16th January 2023) - Harris, Zoey; Kaizer, Hannah; Wei, Aria; Karantanos, Theodoros; Williams, Donna M.; Chaturvedi, Shruti; Jain, Tania; Resar, Linda; Moliterno, Alison R.; Braunstein, Evan M.
Summary: The aim of this study was to compare the genomic features and clinical outcomes between paediatric and young adult patients (PAYA, <40 years) and older adults (OA, ≥40 years) with myeloproliferative neoplasms (MPN) to gain insight into pathogenesis, disease prognosis and management. Of 630 MPN patients, 171 (27%) were PAYA with an average age at diagnosis of 31 years. Females were more prevalent in PAYA than OA (71% vs 58%; p = 0.002), and PAYA more frequently presented with essential thrombocytosis (ET) at diagnosis (67% vs 39%; p < 0.001). The presence of a JAK2 somatic mutation was higher in OA (80.4% vs 64.3%; p < 0.001), while a CALR mutation or lack of any traditional driver mutation was more common in PAYA (20.5% vs 10.5%; p = 0.001, 8.8% vs 3.7%; p = 0.01 respectively). Venous thrombosis was more common in PAYA compared to OA (19.8% vs 10.7%; p = 0.002). PAYA had a higher prevalence of familial MPN and familial cancer predisposition, and two PAYA patients harboured pathogenic germline JAK2 lesions. PAYA demonstrated longer survival from diagnosis than OA (median not reached vs 13 years), while disease transformation was less frequent (19.3% vs 37.9%).